스마트하우징 활성화를 위한 건설 분야의 연구동향 분석 : 등재학술지를 중심으로(2000~2020) - 이종호(Jongho Lee); 황은경(Eun Kyoung Hwang); 서동구(Donggoo Seo); 이재욱(Jaewook Lee) (KIEAE Journal, 2021)
Purpose: With the spread of the 4th industrial revolution technology, the change of the housing paradigm is accelerating, and the development of technology is required according to the related to the smart home. Although many studies on smart homes have been conducted in Korea, there are insufficient cases of systematically analyzing and reviewing these studies.The purpose of this study is to investigate the domestic research cases of smart home in detail and to analyze the research trends by major keywords using a systematic table of these research cases. In this process, leading keywords related to government policies, market trend can be extracted and the flow of major research related to smart homes that have been conducted since the early 2000s is reviewed. Method: This study examines a number of previous studies in Korea. In particular, changes in similar keywords related to ‘smart home’ and the trend of smart home development are analyzed according to the development of related technology. To this end, the results of 556 studies conducted in the DBPIA search engine are collected and the research contents are analyzed. Result: The analysis can be summarized as follows. (1) Research on smart home can be clustered into four categories (construction, communication, home appliance, service). Based on these major items, detailed elements are classified and keywords for research and technology development are suggested. (2) The smart home-related construction field can be divided into four sub-elements (planning, equipment, energy, law) in detail, and research trends of related papers are introduced using a systematic table. KCI Citation Count: 1